Antimicrobial Effect of Alpha Lipoic Acid Against Oral Microorganisms. - S , SHEBI; D, EZHILARASAN (The journal of contemporary issues in business and government, 2020)
Aim: This study was aimed to assess the antibacterial effect of alpha lipoic acids against various oral microorganisms. Background: Oral microorganisms are responsible for oral related diseases.Oral microorganisms implicated in the etiology of dental caries, stomatitis, gingivitis and periodontitis. Gradual increase in the rate of resistance to antibiotics leads to increase in oral pathologies.. Materials and method: 100 mg of alpha lipoic acid was measured and dissolved in 2 ml of ethanol. 250 ml of Muller Hinton Agar (MHA) was prepared, sterilised, poured onto the petri plates. After solidification each MHA plates were swabbed by overnight culture of enteric organisms such as Staphylococcus aureus, Streptococcus mutans, Pseudomonas species, Enterococcus faecalis, Escherichia coli, Candida albicans. Using a well cutter 3 wells were formed on each MHA plate. In each well, alpha lipoic acid was added at the concentration of 30, 60 and 90 ul and the petri plates were kept for incubation at 37 °C for 24 h. The zone of inhibition was recorded in each plate Result: Alpha lipoic acid prominently inhibited the growth of all the organisms invested. It possesses inhibitory antimicrobial effects even at low concentrations and it has shown maximum inhibitory antimicrobial activity at higher concentrations. Candida albicans was found as highly susceptible to alpha lipoic acid. Conclusion: The potential use of alpha lipoic acids provided in a local delivery vehicle to infected sites in the oral cavity, could be considered as an additional therapeutic approach to improve oral health